ST&I dynamics via academic spin-off: evidence of the systemic functional structure of the innovation process (Management and Connections Journal, 2022)
The present research highlights the ST&I dynamics established by an academic spin-off linked to a Brazilian public university, so as to analyze the functional structure of the national innovation system. The objective of the investigation was to identify components, interactions and functions that configured the ST&I dynamics, so as to enable the development of a new technology as an expression of a technological paradigm shift. The study was constituted under a qualitative approach, operationalized through semi-structured interviews, treated based on content analysis. The articulation of different players and competencies was verified to enable the development of the new technology and its transfer to the market. Among these actors, five main domains were identified: University, Development Agencies, Political Actors, Facilitators, and Market. Certain functions, such as Regulation, Support, Infrastructure, Financing and Commercialization, were manifested as key to the generation of innovation.
Keywords: Academic spin-off; Technological innovations; National Innovation System